THE FULFILLMENT OF COMPREHENSIVE CHILD’S RIGHTS TO HEALTH IN CHILD DEVELOPMENT AGENCY (LPKA) OF KARANG ASEM, BALI - Ani Purwanti (Faculty of Law, Universitas Sebelas Maret, 2017)
This article aimed to investigate How is The fulfillment of the right to comprehensive child rights to health in Child Development Agency (LPKA) Karang Asem, Bali. The right to health is one of the rights of children that the State guarantees. The State’s obligation to ensure the fulfillment of the right to health in which is regulated in Article 44 of Law number 35 of 2014 on the Amendment of Law number 23 of 2002 on Child Protection has to be implemented. Unfortunately, however, there is a paradigm of inconsistency between regulations relating to the purpose of parenting and child coaching.Paradigm change of special protection for child in trouble with law as a protégé as regulated in Child’s Protection Law is still different from the Law Number 12 of 1995 on Correctional System. The method used in this study is a qualitative empirical juridical approach. This interdisciplinary method is useful to get a thorough description related to facts of an implementation of a policy and its social impact. The research result concludes that The fulfillment of the right to comprehensive child rights to health in LPKA is the State’s responsibility, in this case are LPKA, Local Government c.q /represented by the Office of Justice and Human Rights and the Office of Health and the Central Government represented by the Ministry of Justice and Human Rights and the Ministry of Health, also society and parents.